Epitaxy (IntechOpen, 2023)
The edited volume "Epitaxy" is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of materials science. The book comprises single chapters authored by various researchers and edited by an expert active in this research area. All chapters are complete in themselves but are united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors in the field of materials science as well as opening new possible research paths for further developments.